2003
DOI: 10.1161/01.cir.0000097115.61309.59
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Pulmonary Edema in Heart Failure

Abstract: Dm decreases after exercise in HF patients but not in control subjects, which suggests a decrease in conductance across the alveolar-capillary barrier, as with pulmonary edema. The reductions were most marked in HF patients with periodic breathing and less reduced in less severe HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
69
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 21 publications
8
69
0
1
Order By: Relevance
“…In HF patients, however, despite the fact that pulmonary perfusion (Q) may be significantly reduced, the ability to appropriately recruit Dm for a given Q preserves the Dm/Q ratio and prevents O2 from significant drops 33 . There is, however, documentation that development of subclinical pulmonary edema during exercise is a common finding in HF patients as suggested by a significant and persistent Dm and Dm/Vc reduction during the recovery phase of exercise 53 . This may result in an increased sensation of dyspnea by activation of J receptor afferents, and there is a suggestion that the DM/Q ratio decreases and significant hypoxemia on exercise develops in some post-transplant patients.…”
mentioning
confidence: 99%
“…In HF patients, however, despite the fact that pulmonary perfusion (Q) may be significantly reduced, the ability to appropriately recruit Dm for a given Q preserves the Dm/Q ratio and prevents O2 from significant drops 33 . There is, however, documentation that development of subclinical pulmonary edema during exercise is a common finding in HF patients as suggested by a significant and persistent Dm and Dm/Vc reduction during the recovery phase of exercise 53 . This may result in an increased sensation of dyspnea by activation of J receptor afferents, and there is a suggestion that the DM/Q ratio decreases and significant hypoxemia on exercise develops in some post-transplant patients.…”
mentioning
confidence: 99%
“…In 25 similar patients, Leite et al 2 reported an average V E/V CO 2 slope of 48.7, which is similar to the 46.6 reported in another study involving 10 patients. 4 Both studies appear far from the V E/V CO 2 slopes of 30 (EOV alone) and 40 (CSA and EOV) reported by Corrà et alThus, in the presence of EOV, a correct V E/V CO 2 slope measure and interpretation should require further mathematical elaboration.These are questions that Corrà et al may help to interpret to further expand our knowledge on the complex and fascinating relationships among exercise ventilation inefficiency, sleep disorders, and life expectancy across different chronic heart failure populations. …”
mentioning
confidence: 78%
“…The main HF symptoms are dyspnea, physical activity intolerance and quality of life reduction [2,3]. HF represents the main cause for hospital ad mission in indiv iduals aging 65 and beyond.…”
Section: Introductionmentioning
confidence: 99%